Role and Place of Higher Specialized Courts in the Judicial System of Ukraine - V. V. Chumak (Bulletin of Kharkiv National University of Internal Affairs)
The role and place of higher specialized courts in the judicial system of Ukraine have been studied and determined. The author has studied such main categories as “judicial system of Ukraine”, “judiciary”, “judicial system” and “judicial power”. The judicial system of Ukraine has been established. The normative and legal base of functioning of highest specialized courts of Ukraine has been characterized. The author has provided own definition of the categories “judicial system of Ukraine” and “judicial power of Ukraine”.